Prazo de entrega em gerenciamento de projetos: um estudo a partir dos dep??sitos de patentes - Ruas, Osmar Borges (2017)
The delivery time is the time unit that determines the time needed to complete the project, which in external or internal conditions in organizations can cause deviations to the project deliveries. As a consequence, they can cause financial loss, excessive expenses, increased risks, communication failures, loss of quality among other problems. In some studies, alternatives are used to avoid or solve these problems in carrying out project management. As an alternative, this study uses about 100 million patents registrations deposited in the European Patent Office (EPO) Espacenet for potential solutions to deadline issues. The objective of this research is to identify the solutions for the delivery time of project management in the EPO base using the extraction of patents with the tool Patent2NET. With open source tooling, it allows for content analysis and bibliographic organization with mind maps. This research uses the qualitative method, with exploratory-descriptive character, with the analysis of secondary data. The correlation, similarity and frequencies of the words will be analyzed. Thus, contributions are offered to improve the understanding of these solutions found in four semantic classes, as well as the presentation of the techniques for constructing search expressions and the patents that can help in the solution of problems of the deadline and, therefore, to promote improvements in project management practices.